The Impact of International University Transnational Social Media Brand Image on Student Brand Attitudes - Ma, Junrui; Adis, Azaze-Azizi Abdul (International Review of Management and Marketing, 2026)
This paper aimed to examine the relationship between international university brand image and brand attitudes in transnational social media environment. The author analyzed the concepts of international university brand image on transnational social media; and expanded the dimensions of international university brand image in this context. Based on the Biel brand image model, a new model was tested using PLS-SEM analysis involving 390 respondents from China. In China’s social media environment, among the four dimensions of international university brand image, university image and source country image significantly and positively affect Chinese students’ brand attitudes. Student image and product or service image have no significant impact on brand attitudes. Based on the Biel brand image model, this study extended the understanding of brand image in the context of transnational social media marketing. It addressed the knowledge gap regarding how international university brand image relates to brand attitude on these platforms.